EFEKTIVITAS PEMBERIAN NIGELLA SATIVA OIL PENCEGAHAN LUKA DEKUBITUS PADA PASIEN TIRAH BARING LAMA DI RUANG ICU RSUD PAMBALAH BATUNG AMUNTAI - Muhammad Riduansyah; Novie Ahdiyat (CNJ: Caring Nursing Journal, 2022)
Decubitus is a problem faced by chronic disease patients, very weak patients, and patients who have been paralyzed for a long time, even now it is a secondary suffering experienced by many hospitalized patients, especially in the ICU. Objective: To determine the effectiveness of administering nigella sativa oil on the prevention of pressure sores in patients on prolonged bed rest in the ICU room at Pambalah Batung Amuntai Hospital. Methods: The research design used in this study is a quasi-experimental design with a nonequivalent control group design that provides pretest and posttest. The population in this study amounted to 35 people. The scale used in the decubitus assessment is the Northon Scale. Results: the most pretest results were in the category of prone to decubitus (12-15) as many as 12 people (80%) and high risk of developing pressure sores (>12) as many as 3 people (20%) and after giving nigella sativa oil with posttest results obtained that the most in the no risk category for pressure sores (16-20) as many as 8 people (53.3%), the vulnerable category for pressure sores (12-15) as many as 6 people (40%) and the high risk category for pressure sores (>12) as many as 1 person (6.7%). Conclusion: Based on the research conducted, there was an effect between before and after administration of nigella sativa oil on the prevention of pressure sores in patients on prolonged bed rest with the same p-value (0.000 < 0.05).